Orgasmolepsy in Narcolepsy Type 1 Responsive to Pitolisant: A Case Report - Pellitteri, Gaia (Nat Sci Sleep, 2020)
We describe a case of a young male patient with narcolepsy type 1 (NT1), who developed generalized cataplexy attacks during sexual intercourses, on which we have obtained a satisfactory control with pitolisant. Orgasmolepsy is an uncommon feature of NT1 that has been poorly described in the literature. The prevalence of this condition is unclear, as it is reasonably underreported by patients for embarrassment and not well investigated by physicians. Pitolisant is a novel treatment for narcolepsy, effective on excessive daytime sleepiness and cataplexy by modulating the histaminergic system. Real-world data collection on pitolisant efficacy and safety is still ongoing. However, pitolisant effectiveness on orgasmolepsy in NT1 has no precedent in the literature. Orgasmolepsy and other sexual disturbances should be actively searched in narcoleptic patients and, if present, may guide clinicians to prefer pitolisant or sodium oxybate, avoiding antidepressants for their possible sexual side effects.